1999
DOI: 10.1111/j.1475-2743.1999.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization from nitrogen fertilizers with and without gypsum

Abstract: Ammonia volatilization with and without gypsum incorporation was measured in Gujranwala soil (Udic Haplustalf) in an incubation study using different nitrogen fertilizers e.g. urea, ammonium sulphate (AS), calcium ammonium nitrate (CAN), and urea nitrophos (UNP). Nitrogen from different fertilizers was applied at the rate of 200 mg N kg 71 to two sets of soils in plastic bags (1.0 kg soil) and plastic jars (0.5 kg soil). Soil moisture was maintained at field capacity. Application of urea increased soil pH to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
2
0
0
1
Order By: Relevance
“…The majority (80-96%) of N was lost within a short period (24 h to 7 days after application; Figs. 1, 2 and 3), and this finding was consistent with the soil science literature (He et al 1999;Zia et al 1999;Liu et al 2007a, b). The BRS samples used in this study were obtained directly from the refinery and as such exhibited a very high pH (>11 originally) and little biological activity (e.g.…”
Section: Nh 3 Volatilisationsupporting
confidence: 91%
“…The majority (80-96%) of N was lost within a short period (24 h to 7 days after application; Figs. 1, 2 and 3), and this finding was consistent with the soil science literature (He et al 1999;Zia et al 1999;Liu et al 2007a, b). The BRS samples used in this study were obtained directly from the refinery and as such exhibited a very high pH (>11 originally) and little biological activity (e.g.…”
Section: Nh 3 Volatilisationsupporting
confidence: 91%
“…This result can be attributed to the increase in nitrogen availability due to decreasing soil pH caused by application of the used soil amendments. This result is in harmony with those of Zia et al ( 1999) who found that application of gypsum to soil may substantially improve N use efficiency for crop production by reducing nitrogen losses. El-Masry (2001) and Mahmoud et al (2008) concluded that the efficiency of N fertilization can be improved through blended fertilization with Ca 2+ nutrition under moderate saline soil conditions.…”
Section: Macronutrient Uptake:-nitrogen:-supporting
confidence: 88%
“…Além disso, a incorporação do gesso nos tratamentos com uréia, para complementar a quantidade de S aplicada nos tratamentos que receberam sulfato de amônio, pode ter diminuído também a volatilização de N-NH 3 da uréia. Segundo ZIA et al (1999) em um estudo de incubação utilizando fontes de N, no Paquistão, a incorporação de gesso reduziu significativamente as perdas de amônia por volatilização.…”
Section: Resultsunclassified